Dampak Pembinaan Pencak Silat Terhadap Perilaku Sosial di SMP IT Bina Anak Bangsa Kota Palu - Kristanti Liloi, Delvi; Murtono, Tri; Purwanto, Didik; Sukrawan, Nyoman; Alex Suhendra, Tesa (Jurnal Porkes, 2024)
The purpose of the study was to examine how the impact of pencak silat coaching on social behavior at Bina Anak Bangsa IT Junior High School. This research method is a comparative research. The population of this study was 17 students and determined the sample using probability sampling technique. The research instrument used a Likert scale questionnaire to measure students' social behavior. The data collection technique uses calculating the overall questionnaire, questionnaire indicator criteria, % per questionnaire indicator. The data analysis technique uses data processing and analysis carried out in a quantitative way using descriptive-analytical statistics. The results of the Independent T-Test test obtained P-Value Sig. (2-tailed) 0.001 where the value is smaller than 0.05 so that the hypothesis is rejected. That there are results of significant differences between social behavior tends to be high with a percentage of 41.1% compared to the social behavior of students who do not participate in activities tends to be low with a percentage of 47%. The conclusion that there are differences in social behavior between the two variables. It can be said that extracurricular pencak silat coaching activities can have a positive influence on the social behavior of students.